Students’ Perception on the Use of Social Media in Learning English - Pratiwi, Ayu; Ariyani, Amra; Asriati, Asriati (Journal of Excellence in English Language Education, 2025)
This study investigated the perceptions of 10th grade students regarding the use of social media platforms, specifically YouTube and Instagram, in learning English at SMK Negeri 6 Takalar. Social media has gained a significant role in modern educational settings, allowing students to access diverse and engaging language learning materials outside the traditional classroom environment. Using a qualitative descriptive approach, data were collected through semi-structured interviews with ten purposively selected students. The interviews aimed to capture students’ experiences and views on integrating social media into their English learning process. The study revealed that Instagram was the most frequently used platform for learning English, while YouTube served as an additional resource to improve various language skills. Students highlighted that both platforms provided rich visual content and contributed to the improvement of their pronunciation, vocabulary, and listening comprehension. Despite the benefits, some challenges emerged such as poor network quality, limited internet access, and the intrusive nature of advertisements on these platforms. Based on the result, it can be concluded that students have positive perception on the use of social media in learning English.